Production of isomaltooligosaccharides from banana flour - Suwimol Chockchaisawasdee (2018)
Background: Banana is one of the important crops native to tropical Southeast Asia. Since overproduction frequently leads to excessive waste of produce, alternative uses are continuously sought in order to utilise fruits at all stages of maturity. The aim of this study was to investigate the production of isomaltooligosaccharides (IMOs) from banana flour. Results: Banana slurries liquefied by Termamyl SC and saccharified by either Fungamyl 800 L or barley β-amylase were used for IMO synthesis by Transglucosidase L. After 12 h of transglucosylation, maximum IMO yields of 76.67 ± 2.71 and 70.74 ± 4.09 g L -1 respectively were achieved.Although the yieldswere comparable, the IMOprofiles obtained through the use of the two saccharification enzymes were different. Glucose andmaltose were removed by 10 g L -1 bakers' yeast fermentation for 12 h. Regarding total sugars, the final IMO mixture was composed of 53% isomaltotriose, 21% isomaltotetraose and 26% maltooligoheptaose and larger oligomers. Conclusion: Banana flour could be used as a potential rawmaterial for IMO synthesis. © 2012 Society of Chemical Industry.